(untitled) (Fiep Bulletin - online, 2013)
Introduction: It is known that the technical courses enable employment opportunities for individuals outside of higher education and looking for professional qualification. The demand for technical nursing career has increased and by Pibid teachers and academics UNIOESTE interact in this environment, seeking to understand how the teaching-learning process. Objectives: know the profile of students entering technical nursing in a public school Cascavel - PR in 2012, as well as to know the reasons for choosing this course. Methodology: This was a descriptive and exploratory study, conducted with students entering the course in the first semester of the year 2012 in the morning and evening, to which they responded to a questionnaire which had questions: "Why did you choose the technical nursing career?” and “What is your expectation for the course”. The data was analyzed qualitatively. Results: Of the 77 respondents, 75 were female and 2 males, 40 are aged between 18 and 27 years, 25 between 28 and 38 years, 8 between 39 and 49 years, 3 has aged more than 50 years and not one responded, 43 subjects have no employment, working 33 and 1 person did not respond. It is understood that the students chose the course affinity with healthcare, because they enjoy taking care of people and the opportunity to enter the labor market. As for expectations for the course, students want to get a good learning thus become qualified professionals. Conclusion: This study profiled students, apprehended their desires and expectations and provided the results to the school community thus contributing to possible improvements in teaching, since the educational practices must be permeated by the context of lives students.